Inter-rater reliability of DartfishTM movement analysis software for measuring maximum flexion and extension at the hip and knee in older adults with osteoporosis and osteopenia. (3rd June 2019) - Allen, Tyler; Hollingham, Zachary; MacWhirter, James; Welsh, Mark; Negm, Ahmed; Adachi, Jonathan D.; MacIntyre, Norma J.
ABSTRACT: Various methods are used to measure hip and knee joint motion angles; however, their use is often limited by cost or inability to measure dynamic movements. The assessment of movement patterns is clinically useful in individuals with osteoporosis (OP) and osteopenia (OPe) through its potential to optimize fracture risk assessment. This study evaluates the inter-rater reliability of using Dartfish TM 2-D Motion Analysis Software to measure maximum flexion and extension angles at the hip and knee in individuals with OP or OPe while performing five tasks of the Safe Functional Motion test. Twelve participants were videotaped performing the pour, footwear, newspaper, sweep, and sit-to-floor tasks. Five raters used Dartfish TM to analyze maximum flexion and extension angles at the hip and knee, and an intra-class correlation coefficients (ICC) and SEM were calculated for each measurement. In all five tasks, ICC and SEM values ranged from 0.23 to 0.95, and 1.75 to 11.54 degrees, respectively, with maximum knee flexion angles generally having higher ICC, and lower SEM point estimates. The results indicate that Dartfish TM measurements of maximum knee flexion angles in uniplanar tasks demonstrate a moderate to excellent degree of inter-rater reliability, while measurements at the hip joint should be used with caution. Given that the results of this study display moderate to excellent reliability, they lay the groundwork for future research aimed at determining the validity of these measurements. Such research would help to further develop the base of evidence surrounding the usefulness of Dartfish TM Motion Analysis in fracture risk analysis among individuals with OP.